1997
DOI: 10.1016/s0025-3227(97)00015-7
|View full text |Cite
|
Sign up to set email alerts
|

The Brazilian sea-level curves: a critical review with emphasis on the curves from the Paranaguáand Cananéia regions

Abstract: Relative sea-level curves for the mid-to late-Holocene have been proposed for eight different sectors along the Brazilian coast. This paper aims to review the data used to construct the curves proposed for two sectors, the ParanaguA and Canankia regions in southeast Brazil. More specifically, we analyze the palaeo-sea-level indicators (vermetid tubes, shells, wood fragments and shell-midden deposits) related to (1) the sea-level maximum of the mid-Holocene and (2) the two secondary oscillations that would have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
137
0
53

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(197 citation statements)
references
References 23 publications
7
137
0
53
Order By: Relevance
“…The lake forms part of a series of coastal aquatic systems that originated about 7000 years BP, after the first large Holocene marine transgression (Martin and Suguio 1992;Angulo and Lessa 1997;Isla 1998). This transgression was a consequence of glacioeustatic processes, and there were no significant changes in tectonic/seismic activity in the eastern coast of South America during the Holocene (Martin and Suguio 1992;Espinosa et al 2003).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The lake forms part of a series of coastal aquatic systems that originated about 7000 years BP, after the first large Holocene marine transgression (Martin and Suguio 1992;Angulo and Lessa 1997;Isla 1998). This transgression was a consequence of glacioeustatic processes, and there were no significant changes in tectonic/seismic activity in the eastern coast of South America during the Holocene (Martin and Suguio 1992;Espinosa et al 2003).…”
Section: Study Areamentioning
confidence: 99%
“…Particularly along the Brazilian coast (Martin and Suguio 1992;Angulo and Lessa 1997;Angulo et al 1999;Lessa et al 2000), a large number of surveys were undertaken to establish relative sea level variations, and a regional model was developed. Such a model postulates that: (a) present mean sea level was first overtaken approximately 7000 years BP; (b) by about 5100 years BP, sea level had risen to 4-5 m above present mean sea level; (c) between 4000 and 3900 years BP, there was a lowering of sea level to slightly below the present; (d) by about 3600 years BP, sea level rose to 3 m above present mean sea level; (e) between 2800 and 2700 years BP, sea level fell again to slightly below the present one; and (f ) at approximately 2500 years BP, a third high sea level occurred (2.5 m above the present one).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the eustatic sea-level rise following the last glacial maximum resulted in a highstand approximately 5.8 ka ago, encroaching in some locations upon Pleistocene highstand barriers (HORN FILHO et al, 1997;CARUSO JR et al, 2000, DOMINGUEZ, 2009). Since then the sea level has fallen 2 to 4 m (SUGUIU et al, 1985;LESSA, 1997;ANGULO et al, 2006;HESP et al, 2009;MCBRIDE et al, 2013;HEIN et al, 2013HEIN et al, , 2014 as a consequence of global isostasy, as demonstrated by MITROVICA and MILNE (2002).…”
Section: Study Areamentioning
confidence: 99%
“…Por exemplo, modelos climáticos indicam diminuição da pluviosidade média ao longo de grande parte do Norte, Nordeste e Sudeste do Brasil, mas com tendência oposta na região Sul (Marengo et al, 2010 -Tabela 11-1). No entanto, as previsões de aumento de temperatura média e elevação do nível do mar são consistentes em todo o território nacional e suas regiões costeiras (Angulo & Lessa, 1997;Meier et al, 2007;Raicich, 2008;. A partir das projeções climáticas disponíveis, o GT procurou por modelos biológicos (i.e.…”
Section: Introductionunclassified